(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Foreign Direct Investment (FDI) or foreign investment refers to the net inflows of investment toacquire a lasting management interest (10 percent or more of voting stock) in an enterprise operating in aneconomy other than that of the investor. It is the sum of equity capital, reinvestment of earnings, otherlong-term capital, and short-term capital as shown in the balance of payments. It usually involvesparticipation in management, joint-venture, transfer of technology and expertise. There are two types ofFDI Inward Foreign Direct Investment and Outward Foreign Direct Investment, resulting in a net FDI inflow(positive or negative) and Stock of Foreign Direct Investment, which is the cumulative number for agiven period. Direct investment excludes investment through purchase of shares. FDI is one example ofinternational factor movement. An investment abroad, usually where the company being invested in iscontrolled by the foreign corporation. The simplest explanation of FDI would be a direct investment by acorporation in a commercial venture in another country. A key to separating this action from involvementin other venture in foreign country is that the business enterprise operates completely outside theeconomy of the corporation’s home country.